A study on the management of receivables in the period of recession (a developer's experience) - Hasan, Ramli (1986)
Housing sales are normally supported by end-finance. End-financiers are usually a group of institutional lenders such as banks and finance companies arranged by the developer to help potential purchasers. Eligible government employees are usually entitled to 100% housing loan. Purchasers from the private sector rely heavily on end-financing from their employers or banks. Institutional lenders do not provide 100% loan. The maximum they are willing to provide is 90%. The remainder will have to be forked out from the purchasers' own pocket.